Development and characterization of tortilla from squash (Cucurbita maxima var Suprema) flour. - Ermoso, Michelle Constantino
Squash flour was processed from the pulp of mature squash (Cucurbita maxima var Suprema) and utilized as substitute for wheat flour in the production of tortillas. The study aimed to produce tortilla using squash-wheat flour combinations. Three formulations of Squash Flour (SF) and All-Purpose Flour (APF) were prepared, namely F1 (25%, SF, 75% APF), F2 (35%, SF, 65% APF), and F3 (50% SF, 50% APF), and assessed as Tortilla Wrap and Tortilla Chips. Kramer?s Rank Sum test at P0.05 showed no significant differences in rank of the three formulations. However, 2-Sample T-test at P0.05 identified F2 as most preferred for Tortilla Wrap and F1 as most preferred for Tortilla Chips. Formulation 2 was yellow brown in color with slight to moderately perceivable squash flavour, slight chewy texture and slight smooth mouthfeel, and had a general acceptability rating of ?like moderately?. The physicochemical analyses of Formulation 2 showed moisture, crude fiber, water activity, pH, and Vitamin A content of 21.29%, 2.09%, 0.86, 5.89 and 74.16 IU, respectively. Paired Preference test showed significant difference (P.0.0041) between F2 and the control, with the former as most preferred for Wrap. Formulation 1 as the most preferred for Tortilla Chips was yellow brown in color with moderately perceivable squash flavour, moderately crispy texture and a neither rough nor smooth mouthfeel, and had general acceptability rating of ?like moderately?. Formula 1 had a moisture, crude fiber, aw, pH, and Vitamin A content of 2.22%, 1.45%, 0.42, 5.23, 59.4 IU. As Chips, no significant difference existed between F1 and control. Squash flour in Tortilla formulation for wrap and chips proved viable based on the general acceptability of ?liked moderately? for both products. The addition of squash flour improved the value of Tortilla by significantly increasing its fiber and Vitamin A content.